Reinforcement of orthogonal ties in steel-fiber-reinforced reactive powder concrete anchorage zone. Issue 10 (July 2019) - Geng, Xiangri; Zhou, Wei; Yan, Jiachuan
Experiments were performed to investigate the behavior of prismatic blocks with steel-fiber-reinforced reactive powder concrete subjected to centrally applied pressure in a limited area. The objective was to understand the reinforcement effect of orthogonal ties in reactive powder concrete anchorage zone. The three experimental variables were the volumetric ratio of the orthogonal ties, ranging from 4.63% to 5.83%; the ratio of the gross supporting area A b to the bearing plate area A l (local area aspect ratio); and the ratio of core area A cor to the bearing plate area A l (core area aspect ratio). The steel-fiber ratio by volume was 2%. Block behavior in terms of cracking and crack width is related to the bridging effect of the steel fibers and the confining influence of the orthogonal ties. No visible crack and constant stiffness of the specimen prior to cracking were observed. Possible brittle failure was improved to ductile failure, as measured by appearance of major cracks on the sides and ends of the blocks. The orthogonal ties have distinct effect of confining the core of the reactive powder concrete when the ratio of the area of the bearing plate to the area of the reactive powder concrete core surrounded by the orthogonal ties exceeds 1.0.